Built-in TTF–TCNQ charge-transfer salts in π-stacked pillared layer frameworks. Issue 17 (12th April 2017) - Sekine, Yoshihiro; Tonouchi, Masanori; Yokoyama, Taiga; Kosaka, Wataru; Miyasaka, Hitoshi
Abstract : A series of π-stacked pillared layer framework with a formula of (TTF) n [{Rh2 }2 TCNQ] ( n = 1 or 2) was constructed from the assembly reaction between a TTF + TCNQ − salt and paddlewheel-type [Rh2 ] complexes. Abstract : A TTF–TCNQ charge-transfer salt was incorporated in a layer structure with paddlewheel-type carboxylate-bridged dirhodium(ii, ii ) complexes ([Rh2 ]) to construct π-stacked pillared layer frameworks of formula (TTF) n [{Rh}2 (TCNQ)] ( n = 1 or 2).